Long‐term results of robotic‐assisted nasopharyngectomy for recurrent nasopharyngeal carcinoma. Issue 8 (1st June 2022) - Tsang, Raymond K.; Chan, Walter C. P.; Holsinger, Floyd Christopher; Chung, Joseph C. K.; Chow, Velda L. Y.; Chan, Jimmy Y. W.; Ho, Wai‐Kuen; Wei, William I.
Abstract: Background: We have previously reported our early experience in robotic‐assisted nasopharyngectomy. The current case series is a report of our experience in 33 robotic‐assisted nasopharyngectomy. Methods: Prospective series of patients who underwent robotic‐assisted nasopharyngectomy for local recurrent nasopharyngeal carcinoma from January 2010 to March 2019. Results: Thirty‐one patients underwent robotic‐assisted nasopharyngectomy with two additional second procedure for positive margin. Median age is 55 years (29–85). Twenty‐five patients had rT1 disease and six patients had tumor invaded sphenoid floor (rT3). Median operative time was 227 min and median blood loss was 200 ml. The median follow‐up period for all patients were 38 months. Four patients had local recurrence. Five‐year local control rate, overall survival, and disease‐free survival are 85.1%, 55.7%, and 69.1%, respectively. Conclusion: Robotic‐assisted nasopharyngectomy for recurrent nasopharyngectomy was showed to have a high local control rate. The operating time was comparable to open surgery.